Unsteady MHD Flow of Non-Newtonian Fluid in a Channel Filled with a Saturated Porous Medium with Asymmetric Navier Slip and Convective Heating - Rundora, L; Makinde, O. D (Applied Mathematics & Information Sciences, 2018)
This paper aims to computationally study the effects of Navier slip on an unsteady hydromagnetic ﬂow of a pressure driven, reactive, variable viscosity, electrically conducting third-grade ﬂuid through a porous saturated medium with asymmetrical convective boundary conditions. It is assumed that the chemical kinetics in the ﬂow system is exothermic and that the asymmetric convective heat exchange with the surrounding medium at the surfaces follows Newtons law of cooling. The coupled nonlinear partial differential equations governing the ﬂow and heat transfer are derived and solved numerically using a semi-implicit ﬁnite difference scheme. The ﬂow and heat transfer characteristics are analyzed graphically and discussed for different values of the parameters embedded in the system. It is observed that the lower wall slip parameter increases the ﬂuid velocity proﬁles. The upper wall slip parameter is seen to retard the velocity proﬁles while it increases the ﬂuid temperature proﬁles. The wall slip parameters increase the skin friction and the Nusselt number. The wall slip parameters as well as the variable viscosity parameter, the viscous heating parameter and the numerical exponent m reduce the thermal criticality values of the reaction parameter.
Article published in the Applied Mathematics & Information Sciences
Keywords: Unsteady MHD ﬂow; Porous medium; Third grade ﬂuid; Navier slip; Convective heating; Finite difference method; Applied mathematics